Existence of local and global solutions of fractional order differential equations - Muslim, M.; Conca, C.; Agarwal, R.P. (Нелінійні коливання, 2011)
In this paper we shall study the existence of local and global mild solutions of the fractional order differential equations in an arbitrary Banach space by using the semigroup theory and Schauder’s fixed point theorem. We also give some examples to illustrate the applications of the abstract results.